The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12987-017-0059-0
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated differentiation of human induced pluripotent stem cells to blood–brain barrier endothelial cells

Abstract: BackgroundDue to their ability to limitlessly proliferate and specialize into almost any cell type, human induced pluripotent stem cells (iPSCs) offer an unprecedented opportunity to generate human brain microvascular endothelial cells (BMECs), which compose the blood–brain barrier (BBB), for research purposes. Unfortunately, the time, expense, and expertise required to differentiate iPSCs to purified BMECs precludes their widespread use. Here, we report the use of a defined medium that accelerates the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
186
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(201 citation statements)
references
References 45 publications
(88 reference statements)
9
186
1
Order By: Relevance
“…However, one of the studies reported a significant decrease in discontinuous junctions [27]. Other iPSCderived BBB models have reported an increase in permeability of rhodamine 123 of 40%-50% after treatment with P-gp inhibitors [26,27], which is slightly higher than the 28% observed in our model. Similar to our results, these studies do not show changes in P-gp efflux activity between monoculture and coculture.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…However, one of the studies reported a significant decrease in discontinuous junctions [27]. Other iPSCderived BBB models have reported an increase in permeability of rhodamine 123 of 40%-50% after treatment with P-gp inhibitors [26,27], which is slightly higher than the 28% observed in our model. Similar to our results, these studies do not show changes in P-gp efflux activity between monoculture and coculture.…”
Section: Discussioncontrasting
confidence: 79%
“…In terms of functionally restricting permeability iPSC‐EC1 in coculture showed highest performance with high TEER, low NaF permeability, and functional efflux, comparable to other models using similar protocols to derive EC . However, the measured TEER values are lower than some of the highest reported values for iPSC‐derived ECs , and previous reports demonstrate that different iPSC lines give different maximum TEER . iPSC‐EC2 showed substantially lower TEER and higher NaF than iPSC‐EC1, however, in the same range as hCMEC/D3 and other models using similar protocols to derive EC for BBB models .…”
Section: Discussionsupporting
confidence: 65%
“…Previous publications have extensively validated the iBBB cells produced by this differentiation protocol (Hollmann et al, 2017;Lippmann et al, 2012); to determine that the 22q11.2 deletion did not affect the differentiation process, we confirmed similar expression levels in vasculature-specific molecules by flow cytometry (Supplementary Figure 2), and in junctional proteins by immunofluorescence (Supplementary Figure 1A) and western blot (Figure 2A).…”
Section: Differentiation Of Ipscs Into Blood-brain Barrier Endotheliumsupporting
confidence: 78%
“…HiPSCs were differentiated into BBB-like endothelium following the protocol previously published (Hollmann et al, 2017;Lippmann et al, 2012). In brief, HiPSCs were plated onto Matrigel (Corning 354230) coated 6 well TC-treated plated (Falcon 353046) at 100,000 cells/well in Stem MACs iPS-Brew XF media.…”
Section: Differentiation Of Ipscs Into Blood-brain Barrier Endotheliummentioning
confidence: 99%
See 1 more Smart Citation